2019
DOI: 10.1158/0008-5472.can-18-3962
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor Microenvironment Innately Modulates Cancer Progression

Abstract: Cancer development and progression occurs in concert with alterations in the surrounding stroma. Cancer cells can functionally sculpt their microenvironment through the secretion of various cytokines, chemokines, and other factors. This results in a reprogramming of the surrounding cells, enabling them to play a determinative role in tumor survival and progression. Immune cells are important constituents of the tumor stroma and critically take part in this process. Growing evidence suggests that the innate imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
1,651
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 2,188 publications
(1,854 citation statements)
references
References 100 publications
15
1,651
0
3
Order By: Relevance
“…A large body of literature now provides numerous examples of stromal influence on malignant cell function 25,26 , confirming more than a century of speculation about the critical role of the stroma 1 . However, our knowledge remains largely anecdotal and based mostly on work in animal models rather than human subjects.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A large body of literature now provides numerous examples of stromal influence on malignant cell function 25,26 , confirming more than a century of speculation about the critical role of the stroma 1 . However, our knowledge remains largely anecdotal and based mostly on work in animal models rather than human subjects.…”
Section: Discussionmentioning
confidence: 93%
“…During the past two decades numerous studies have revealed interactions between malignant cells and the stroma that promote diverse tumor functions including angiogenesis 4,5 , metastasis 6 , and immunosuppression 7,8 . Stromal cells differ between patients and tumor types [9][10][11][12][13][14][15] and the abundance of certain stromal cell populations are used in the clinic as biomarkers [16][17][18][19] and therapeutic targets [20][21][22][23][24][25] . These studies motivate direct measurements of cell types and the interactions between them in human subjects.…”
Section: Introductionmentioning
confidence: 99%
“…The tumor microenvironment (TME) is defined as the totality of normal cells, molecules and blood vessels surrounding and feeding each cancer cell [146]. TME cells are stromal cells, immune-inflammatory cells and vascular endothelial cells.…”
Section: Resveratrol and Cancer Evidencementioning
confidence: 99%
“…However, the tumor microenvironment is formed from more than just tumor cells, and also includes stromal cells and infiltrating cells of the innate and adaptive immune system, which are likely to also be affected by PARP inhibition. These cells communicate with each other through direct contact and/or indirect signals that can alter the functionality of immune cells so that they either favor or limit tumor growth [10,11]. Emerging evidence supporting the immunomodulatory roles of PARP-1 and PARP-2 has raised the prospect of harnessing PARP inhibition to not only target the cancer itself, but also therapeutically modify its microenvironment.…”
Section: Introductionmentioning
confidence: 99%